Qualitative research a personal skills approach - Shank, Gary D. (Upper Saddle River, New Jersey Merrill/Prentice Hall, 2002)
This up-to-date book is the first of its kind to build upon the basic skills needed to do qualitative research. Skills, such as observing, conversing, participating, and interpreting are introduced through exercises and then developed based on the current understandings in the field. Comprehensive and user-friendly, this book incorporates hands-on learning into the overall process with ten exercises associated with the basic skills. Topics include: Being a Skilled Qualitative Researcher; Observing; Conversing; Participating; Interpreting; Conceptualizing; Reasoning; Analyzing; Narrating; Writing; The Seven Deadly Sins of Qualitative Research; Once and Future Qualitative Research. For qualitative researchers.-- Amazon.
1. Being a skilled qualitative researcher -- 2. Observing -- 3. Conversing -- 4. Participating -- 5. Interpreting -- 6. Conceptualizing -- 7. Reasoning -- 8. Analyzing -- 9. Narrating -- 10. Writing -- 11. The Seven Deadly Sins of qualitative research -- 12. Once and future qualitative research.
PI-8275 donated by Department of Global Development Cornell University Ithaca.
Keywords: Social sciences -- Methodology; Qualitative research